2008
DOI: 10.1080/13554790701851536
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Long-Term Anterograde Amnesia, but Not Retrograde Amnesia, after Initiation of an Anti-Epileptic Drug in a Case of Transient Epileptic Amnesia

Abstract: Transient epileptic amnesia (TEA) is characterised by recurrent brief episodes of amnesia and atypical amnesic symptoms, known as long-term anterograde amnesia and dense retrograde amnesia. It has been proposed that an antiepileptic drug (AED) can prevent not only epileptiform activity, but also accelerated forgetting. However, there have been no reports regarding the effects of such drugs on retrograde amnesia. We found that an AED prevented accelerated forgetting, but not dense retrograde amnesia, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…A similar dissociation has been described in a patient with TEA (Midorikawa & Kawamura, 2007). Taken together, these findings suggest that factors giving rise to repeated episodes of transient amnesia can render previously established memories persistently inaccessible or delete them altogether.…”
Section: The Neural Basis Of Autobiographical Amnesiasupporting
confidence: 55%
See 1 more Smart Citation
“…A similar dissociation has been described in a patient with TEA (Midorikawa & Kawamura, 2007). Taken together, these findings suggest that factors giving rise to repeated episodes of transient amnesia can render previously established memories persistently inaccessible or delete them altogether.…”
Section: The Neural Basis Of Autobiographical Amnesiasupporting
confidence: 55%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 The second key theoretical question is whether ALF results from a structural pathology of the episodic memory system or can be caused by a purely physiological -and therefore fully reversible -disturbance. There have been reports of improvement or resolution of ALF on treatment of seizures (Midorikawa & Kawamura, 2007;O'Connor, Sieggreen, Ahern, Schomer, & Mesulam, 1997), supporting a physiological explanation, but ALF often persists in patients whose clinical seizures have ceased (Butler et al, 2007). CS's case shows unequivocally that a fully reversible, pharmacological, effect is capable of causing ALF.…”
Section: The Neural Basis Of Alfmentioning
confidence: 99%
“…Mayes et al, 2003;Kapur et al, 1996;Mameniskiene, Jatuzis, Kaubrys & Budrys, 2006). While O'Connor et al (1997) found that anticonvulsant medication improved memory indirectly, through minimising seizures, and Midorikawa and Kawamura (2007) report a case with improvement in ALF under successful anticonvulsant medication, high serum levels of epilepsy drugs have also been shown to impair retention (but not acquisition), of new information (Jokeit, Kramer & Ebner, 2005). Butler and Zeman (2008a) argue that the accelerated forgetting seen in cases of TEA is unlikely to be a direct result of anticonvulsant treatment as patients subjectively report symptoms prior to treatment, and often report improvements after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…La opinión general es que los déficits de memoria retrógrada (autobiográfica) no responden a los fármacos anti-comiciales, sin embargo se ha logrado mejoría del OA en un caso de AET (37).…”
Section: Tratamientounclassified